The Grassroots Energy Transition in Poland through a Sociological Lens - Tyrała, Radosław; Nawojczyk, Maria; Afeltowicz, Łukasz (Stan Rzeczy, 2025)
An energy transition is underway in Poland. Various socio-technical models of energy production and consumption are being tested, including prosumption, renewable energy generation, and microgrids. However, success has been limited. We show that sociological concepts developed to explain the course of the socio-economic transformation in Poland can easily be applied to Poland’s energy transition. Using such theoretical categories as “sociological vacuum,” “apparent actions,” and institutional isomorphism, we explain the lack of success of the energy transition in Poland in connection with the functioning of different types of energy communities. This text is not a report on empirical research. Although we refer to our empirical research, which we have discussed more extensively elsewhere, the text is theoretical in nature. Our goal is to bring classical sociological categories into the discussion of energy transformations.